Experimental and computational thermochemical study of two fluorobenzazoles: 5-fluoro-2-methylbenzoxazole and 5-fluoro-2-methylbenzothiazole. (May 2018) - Silva, Ana L.R.; Gonçalves, Jorge M.; Ribeiro da Silva, Maria D.M.C.
Graphical abstract: Highlights: Combustion enthalpies for of two fluorobenzazole derivatives have been determined by rotating-bomb combustion calorimetry. Enthalpies of vaporization of two fluorobenzazoles have been determined by the vacuum drop microcalorimetric technique. Gas-phase enthalpies of formation of two fluorobenzazoles were estimated computationally (G3(MP2)//B3LYP level of theory). Energetic properties of 5-fluoro-2-methylbenzoxazole and of 5-fluoro-2-methylbenzothiazole were determined by calorimetry. Comparison experiments performed to characterize the final state of 5-fluoro-2-methylbenzothiazole combustion experiments. Abstract: An energetic study of 5-fluoro-2-methylbenzoxazole (FMBO) and of 5-fluoro-2-methylbenzothiazole (FMBT), in condensed and gaseous states, has been performed using calorimetric techniques and computational calculations. The standard ( p ∘ = 0.1 MPa ) molar enthalpies of formation of FMBO and FMBT, in the liquid phase, at T = 298.15 K, were derived from the corresponding standard molar energies of combustion, measured by rotating-bomb combustion calorimetry. At T = 298.15 K, the standard ( p ∘ = 0.1 MPa ) molar enthalpy of vaporization, for each compound, was determined, by a direct method, using the vacuum drop microcalorimetric technique. For each compound, from this last value and from the enthalpy of formation of the liquid compounds, the corresponding standard ( p ∘ = 0.1 MPa ) enthalpy of formation in the gaseous phase has been calculated. Additionally, the gas-phase standard molar enthalpies of formation of these two compounds were estimated computationally at the G3(MP2)//B3LYP level of theory, as well as their gas-phase basicities and proton affinities.